The Future of Work: Gig Economy, Automation, and Labor Dynamics - Raj, Preeti (Journal of Neonatal Surgery, 2025)
Automation, artificial intelligence, and the gig economy are reshaping work in India. Traditional employment models based on fixed wages and long-term contracts are shifting towards flexible, platform-based, and task-oriented labor. India, with a largely informal workforce, faces both opportunities and challenges in adapting to technological change. This paper examines the impact of AI, automation, and gig platforms on labor rights, informalization, gender, and social security in India. It provides a historical overview of labor transformations, from colonial indenture to digital platform work. It analyzes algorithmic control, income precarity, gendered experiences, and legal ambiguities surrounding platform workers. The paper concludes by offering policy solutions focused on social protection, ethical AI, skill development, and inclusive growth..